Yuuyaraq today, Yuuyaraq tomorrow: modeling erosion threats to Yup’ik traditional land use areas - Sean Gleason; Jonathan Lim; Daniel Marsden; Joe Pleasant; Warren Jones; Willard Church (Journal of Maps, 2023)
ABSTRACTThe following article illustrates the impact of contemporary coastline change on Yup’ik subsistence practices known collectively as Yuuyaraq. We draw from an extensive archive (n = 490) of historic maps, aerial photographs, and surveying reports collected and digitized over the course of on-site visits to Quinhagak, AK from 2018-2021. In addition, our research team conducted numerous recorded (n = 7) and unrecorded (n = 42) interviews with community members about recent environmental changes near Quinhagak to study the impact of coastal erosion. Our aim is to demonstrate how archival maps can provide high quality, mobile-friendly visualizations so that Yupik researchers and community members can study the impact of climate change in the Yukon-Kuskokwim (Y-K) Delta.